Submicron infrared imaging of an oesophageal cancer cell with chemical specificity using an IR-FEL. (8th November 2018) - Ingham, J; Craig, T; Smith, C I; Varro, A; Pritchard, D M; Barrett, S D; Martin, D S; Harrison, P; Unsworth, P; Kumar, J D; Wolski, A; Cricenti, A; et al.
Abstract: This work reports the use of an infrared spectroscopic version of scanning near-field optical microscopy (IR-SNOM) and shows that it is possible to reveal subcellular entities via their chemical constituents in a label-free human oesophageal adenocarcinoma cell (OE33). This work presents the first high spatial resolution (∼0.15 μ m) study of features imaged at various wavelengths within a cancer cell. The clear illumination of sub-micron sized moieties within a cell is a major step forward and is a key requirement for understanding cancer and for the study of other diseases and healthy tissue. The stable and tuneable light source was provided by the infrared free electron laser on the ALICE accelerator at Daresbury. The images reveal a structure with a size and wavelength absorption that are consistent with a chromosome and open the possibility of observing other localized structures, such as microvesicles, that play an important role in the development and spread of cancers.